Healthy Lifestyle Habits in Latin American University Students during COVID-19 Pandemic: A Multi-Center Study - Valdés Badilla, Pablo (2022)
ABSTRACT Background: Deterioration in the health-related quality of life (HRQoL) and healthy eating behavior due to the effect of COVID-19 lockdown has been reported. The aim of this study was to associate eating habits and HRQoL with physical activity behavior in Latin American university students during COVID-19 pandemic. Methods: Measured 4,859 university students with a mean age of 22.4years and they were mostly female (73.7%) from 10 Latin American countries (Argentina, Chile, Colombia, Costa Rica, Ecuador, Guatemala, Mexico, Panama, Paraguay and, Peru). Eating habits were measured using a survey validated with other university students, HRQoL was assessments using the short version of the World Health Organization (WHOQOL-BREF) scale and physical activity behavior with a dicotomous question based on the international recommendations for physical activity. Results: There is a higher complaince for all the international recommendations for healthy foods intake in the physically active group of students (p<0.01), with the exception of alcohol and salt. In addition, physically active students presented a significantly higher HRQoL (p<0.001) in all the dimensions analyzed when compared to physically inactive students. Conclusions: Latin American university students who are physically active are more likely to have a healthier eating behavior and a lower risk of a decreased HRQoL during COVID-19 pandemic.